PENGARUH KOMPETENSI PENDAMPING PROGRAM KELUARGA HARAPAN (PKH) DAN UMKM PESERTA TERHADAP PENINGKATAN PENDIDIKAN ANAK PESERTA PKH DI KECAMATAN CIRUAS KABUPATEN SERANG - Khaeruman, Khaerumam; Mukhlis, Ahmad (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2018)
ABSTRACT his research has a purpose to know and test the influence between Competency Assistant Program of Family of Hope (PKH) and UMKM together to increase education of children of PKH participant in District of Ciruas Regency of Serang. While the research method using quantitative research approach. Based on the results of the study showed that the results of simple correlation analysis (r) using SPSS program version 22 obtained value of 0.144, meaning that the closeness of the relationship between variables Competency Assistant PKH and SMEs on Education Children Participant PKH is strong because the value of 0.144> 0.5 and are in the low range ie (0.00 - 0.20). The amount of independent variable contribution is determined by the coefficient of determination and obtained calculation of 14.4%, meaning that the Competency Assistance variable of PKH and UMKM affects the Education of Child Participant PKH 14.4%, and the rest 85.6% is influenced by other variables not explained in this research model. While the results of hypothesis testing using SPSS program version 22 obtained Fcount value of 12.969 greater than Ftabel of 3.10 and Sig F value of 0.000 smaller than 0.05 then there is a significant influence between Competency Assistance PKH and UMKM simultaneously to the Education of Participant Children PKH in Kecamatan Ciruas, Serang regency. Keywords: Competence, UMKM and Education